Didactic Possibilities of Formation of University Students Professionally Significant Personal Qualities - Platonova, Raisa I.; Lazareva, Larisa P.; Pechenyuk, Anatoly M.; Polichka, Anatoly E.; Ikonnikov, Aleksandr I.; Semenova, Natalya V.; Dvoryankina, Ekaterina K.; Blinov, Leonid V.; Bastrikov, Alexey V. (International Review of Management and Marketing, 2016)
The modern society needs highly educated professionals, who are not only capable of navigating in difficult work situations, working in a team and taking responsibility for the completed tasks’ results, but also willing to take decisions under conditions of frequent change of professional activities’ technologies. The goal of the article is to justify and experimentally verify didactic possibilities of formation of future specialists’ professionally significant personal qualities in the process of students’ professional modules mastering. The leading approach is a design approach that contributes to organization of a focused process for the development of professionally significant personal qualities and the formation of students’ competencies, as well as realizing of professional modules’ potential in the educational process. The authors reveal, justify and experimentally check up didactic possibilities that contribute to the project approach’s effective implementation in the organization of educational process at the University. This article is recommended for teachers, researchers, heads of educational institutions engaged in training of bachelors and masters. Keywords: Higher Education, Project Approach, Professional Modules, Didactic Possibilities. JEL Classifications: A23, I23, I26